Society in need of transformation. Citizen-Foresight as a method to co-create urban future - Wilhelmer, Doris (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2016)
The European Commission highlights that creating shared values and democratic citizenship is a today’s requirement to answer challenges of urbanization in Europe. The awareness about the necessity of inclusion of vulnerable groups such as elderly or migrants is still a substantial deficit in research on inclusion. As a matter of principle, future cannot be forecasted. The most effective way to foresee future is to jointly shape it! The Participatory Citizen-Foresight offers a neutral transformation-room and multi-method coordination-framework for detecting accessible and tacit-knowledge for change. In co-creation citizens, experts and Civil-Servants gain insights into complex interdependencies allowing mutual learning and behavior in rehearsal for transition. Society is in need of powerful, collective pictures serving self-confidence and self-responsibility of citizens. First, we describe the specific, participatory-foresight approach. Second, we highlight preconditions for learning and societal change based on constructivism and brain research. Third, we show how this can work in reality by shortly outlining two Citizen-Foresight cases with elderlies and, fourth, we derive selection- criteria for methods aiming at transforming mental images, maps and behaviour.
Keywords: demographic change; participatory-foresight; citizen-foresight; societal-change